Implementation of a Web-Mobile-Based Cashless Parking Retribution Payment System Using QR Code Method - Firmansah, Ari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The widespread practice of illegal parking in Batam City has led to a decline in Local Own-Source Revenue (PAD) and contributed to disorder in public spaces. The existing manual parking retribution payment system is deemed ineffective in addressing unauthorized fee collection and lacks transaction transparency. This study aims to develop a non-cash parking retribution payment system based on web mobile technology using QR Code methods. The system development method employed is Agile, encompassing the stages of Plan, Design, Develop, Test, Deploy, Review, and Launch. The application was developed using Kotlin for the Android platform and Laravel as the back-end framework, offering features such as QR Code scanning, automatic transaction recording, and a user-friendly interface. Testing results indicate that the system can enhance the efficiency of parking management, reduce direct interaction between users and parking attendants, and strengthen transparency and accountability in the recording of retribution payments. The implementation of this system is expected to serve as a sustainable solution for the modernization of parking services and the improvement of PAD in Batam City.